Adoption of linked data technologies among university librarians in Pakistan: Challenges and prospects - Warraich, Nosheen Fatima; Rorissa, Abebe (Malaysian Journal of Library and Information Science, 2018)
This study aims to explore librarians’ perspective about the adoption of Linked Data technologies along with their level of interest to adopt these technologies in Pakistani university libraries. It also identifies their perceived hindrances that obstruct them to adopt and effectively implement Linked Data technologies in libraries. This is a quantitative study based on survey research design. To meet the objective of the study, a self-constructed and validated questionnaire was used to collect data. Findings show that university librarians believe in the effective adoption of Linked Data technology in libraries. They perceive that Linked Data technology can enhance navigation between the traditional online tools to access library resources and Linked Data will soon be the standard for creating metadata and records for information resources management in libraries. They are eager to attend events about Linked Data application in their libraries and willing to explore ways to incorporate Linked Data standards in bibliographic records management as well. Barriers do exist such as the general lack of awareness of basic Linked Data concepts and best practices for this emerging technology. To foster the research and to set Linked Data best practices in libraries and other cultural heritage institutions, there is a potential to invest in this area in terms of financial and social capital.